Metronidazole induced peripheral neuropathy - Maskey, R; Sharma, SK; Poudel, KN (Health Renaissance, 2011)
Metronidazole is a little known cause of drug-induced neuropathy.We report a patient who developed paraesthesia of both limbs after one month course of metronidazole. The electrophysiologic test confirmed a bilateral motor-axonal neuropathy. This neuropathy improved dramatically with cessation of the drug. Keywords: metronidazole; peripheral neuropathy; hepatic amebiasis DOI: http://dx.doi.org/10.3126/hren.v9i2.4986 Health Renaissance 2011: Vol.9 (No.2): 119-121